Enhanced Amygdala-Striatal Functional Connectivity during the Processing of Cocaine Cues in Male Cocaine Users with a History of Childhood Trauma - Kaag, Anne Marije; Reneman, Liesbeth; Homberg, Judith; van den Brink, Wim; van Wingen, Guido A. (Frontiers in Psychiatry, 2018)
Abstract Background and Aims Childhood trauma is associated with increased levels of anxiety later in life, an increased risk for the development of substance use disorders as well as neurodevelopmental abnormalities in the amygdala and frontostriatal circuitry. The aim of this study was to investigate the (neurobiological) link between childhood trauma, state anxiety and amygdala-frontostriatal activity in response to cocaine cues in regular cocaine users. Methods In this study we included 59 non-treatment seeking regular cocaine users 58 non-drug using controls. Blood oxygenation level dependent (BOLD) responses were measured using functional Magnetic Resonance Imaging (fMRI) while subjects performed a cue-reactivity paradigm with cocaine and neutral cues. Psychophysiological interaction analyses were applied to assess functional connectivity between the amygdala and other regions in the brain. Self-report questionnaires were used to measure childhood trauma, state anxiety, drug use, drug use severity and craving. Results Neural activation was increased during the presentation of cocaine cues, in a widespread network including the frontostriatal circuit and amygdala in cocaine users but not in controls. Functional coupling between the amygdala and medial prefrontal cortex was reduced in response to cocaine cues, in both cocaine users and controls, which was further diminished with increasing state anxiety. Importantly, amygdala-striatal connectivity was positively associated with childhood trauma in regular cocaine users, while there was a negative association in controls. At the behavioral level, state anxiety was positively associated with cocaine use severity and craving related to negative reinforcement. Conclusions Childhood trauma is associated with enhanced amygdala-striatal connectivity during cocaine cue-reactivity in regular cocaine users, which may contribute to increased habit behavior and poorer cognitive control. While we cannot draw conclusions on causality, this study provides novel information on how childhood trauma may contribute to the development and persistence of cocaine use disorder. Keywords: cocaine addiction; anxiety; childhood trauma; functional connectivity; ventral striatum; amygdala; dorsal medial prefrontal cortex; negative reinforcement